Teachers’ construction of meaning and expansion of ideas while sharing teaching strategies during teacher literature circles: A Malaysian school context / Angeline Ranjethamoney Vijayarajoo - Vijayarajoo, Angeline Ranjethamoney (Universiti Teknologi MARA, Kedah, 2017)
Studying literature can be challenging for ESL learners. When the new novel wasintroduced by the Ministry of Education Malaysiain 2015, the teachers’ responses included concern over how they were going to teach their students who found literature difficult and boring. The teachers were also concerned that they would have to look for books to read and add to their own knowledge and understanding, apart from looking for new resources for tests and examination questions. Hence the researcherasked for volunteers to form a Teacher Literature Circle, an informal gathering of teachers to discuss a literary work on a regular basis, in order to facilitate better understanding of the text. Four teachers from an urban school participated in the study. The Teacher Literature Circle (TLC) discussions took place weekly for seven consecutive weeks, each session varying from two to four hours each. Four months after the TLC discussions had ended, the researcher interviewed the teachers.The purpose of the study was to find out how teachers made meaning of the new text during TLC discussions which may also have impacted their classroom teaching experiences and what went on in the classrooms as well as after the teaching was over. Data comprised the transcripts of every TLC discussion and the interview data of the teachers, 4 months later on, after they had completed the teaching of the new text. The findings revealed that from sharing teaching strategies during the TLC, the teachers brought these strategies into the classroom and together with their students’ responses, built on their meanings from the time of the TLC. The teachers con-constructed meaning and expanded earlier ideas from the TLC.